The story of Ferdinand - Leaf, Munro, 1905-1976.; Lawson, Robert, 1892-1957 (New York : Grosset & Dunlap, 2000)
Ferdinand likes to sit quietly and smell the flowers, but one day he gets stung by a bee and his snorting and stomping convince everyone that he is the fiercest of bulls.
Keywords: Bulls -- Fiction